1994
DOI: 10.1039/c39940002483
|View full text |Cite
|
Sign up to set email alerts
|

Efficient glucose detection in anaerobic solutions using an enzyme-modified electrode designed to detect H2O2: implications for biomedical applications

Abstract: The finding that a 'first generation' glucose oxidase modified poly( o-phenylenediamine) coated Pt electrode, designed t o detect H202' responded t o glucose in N2-saturated solutions with a sensitivity similar to that of air-saturated media is of considerable significance for the application of biosensors in biological systems where O2 availability is severely restricted.Ortho-Phenylenediamine (PD , 1,2-diaminobenzene) forms a self-sealing, highly insulating thin (ca. 10 nm) membrane containing trapped enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…These results support our previous in vitro O 2 interference studies (Lowry et al, 1994b) and confirm that Pt/PPD/GOx sensors are not affected by changes in O 2 over physiologically relevant concentration ranges for the brain. A similar lack of O 2 interference has also been observed by other groups; Asai et al (1996) have used glutamate oxidase and a dialysis electrode incorporating a PPD coated Pt wire to monitor brain extracellular glutamate during acute ischemia and found that the sensor operates reliably despite the lack of O 2 around the dialysis electrode and Garguilo and Michael (1994) have found that the availability of O 2 in brain ECF is sufficient for from the reaction of O 2 , the natural cosubstrate for GOx, with the reduced form of the enzyme (GOx/ FADH 2 ) which is generated by reaction with glucose (see reactions 1 and 2 above).…”
Section: Effect Of Oxygen On Biosensor Response In 6i6osupporting
confidence: 91%
See 2 more Smart Citations
“…These results support our previous in vitro O 2 interference studies (Lowry et al, 1994b) and confirm that Pt/PPD/GOx sensors are not affected by changes in O 2 over physiologically relevant concentration ranges for the brain. A similar lack of O 2 interference has also been observed by other groups; Asai et al (1996) have used glutamate oxidase and a dialysis electrode incorporating a PPD coated Pt wire to monitor brain extracellular glutamate during acute ischemia and found that the sensor operates reliably despite the lack of O 2 around the dialysis electrode and Garguilo and Michael (1994) have found that the availability of O 2 in brain ECF is sufficient for from the reaction of O 2 , the natural cosubstrate for GOx, with the reduced form of the enzyme (GOx/ FADH 2 ) which is generated by reaction with glucose (see reactions 1 and 2 above).…”
Section: Effect Of Oxygen On Biosensor Response In 6i6osupporting
confidence: 91%
“…An increase in brain O 2 levels accompanying an insulin induced fall in brain glucose has also been reported by Silver and Ereciñ ska (1994). The different time courses of changes in glucose and oxygen observed with insulin suggest that changing O 2 levels in vivo do not influence the Pt/PPD/GOx signal supporting our previously published in vitro work on O 2 interference (Lowry et al, 1994b). A more detailed investigation of this type of interference is presented below (see Section 3.4).…”
Section: Effect Of Insulin On Biosensor Response In 6i6osupporting
confidence: 78%
See 1 more Smart Citation
“…These attributes include fast response time, linearity over the relevant concentration range, effective elimination of interference by endogenous reducing agents such as ascorbic acid, freedom from protein and lipid fouling, stability in vivo, and ease of miniaturisation (O'Neill and Lowry, 2000). In a preliminary publication, we demonstrated that Pt/ PPD/GOx sensors might also be free of O 2 interference in applications both in vitro and in vivo by showing that they responded to glucose with similar sensitivity over a wide range of pO 2 values in vitro (Lowry et al, 1994b). As this phenomenon has important implications both for the development of biosensors and for their operation in biological systems, where O 2 availability is restricted, we examine it now in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…An important stage in the development of this biosensor was the in vitro and in vivo characterisation of the sensor, which demonstrated that it has a fast response time, is linear over the relevant concentration range, is free of protein and lipid fouling, and has minimal interference from endogenous species (Lowry and O'Neill, 1994;Lowry et a!., 1994b;.…”
mentioning
confidence: 99%